Graphic designer: how to stabilize price range? / Mohd Ikmal Hanif Bokhori - Bokhori, Mohd Ikmal Hanif (Faculty of Art and Design, 2020)
Since gaining independence in 1957, Malaysia has successfully diversified its economy from one that was initially agriculture and commodity-based, to one that now plays host to robust manufacturing and services sectors, In the graphic design world, we still have a problem with putting our service charge to the client. In Malaysia, most of the graphic designer was underpaid from what they give to the client This thing happens because of many reasons, and we must do something before the graphic designer being suppressed event more. A graphic designer does not get paid as they should have because of many factors, and one of them is because of the pricing domino effect. Domino effect has happened when junior graphic designer put lower price for their artwork. This will give a lousy perception to the client about all graphic designer are easy to get and can be paid by a little cost. This will affect every senior designer price rate because most of the client will go for the cheapest one, and once this thing happens, all the price will slowly decrease, and that time domino effect occurs.